1999
DOI: 10.1109/75.769529
|View full text |Cite
|
Sign up to set email alerts
|

A novel on-wafer resistive noise source

Abstract: We describe a novel on-wafer resistive noise source (ORNS) suitable for noise parameter characterization of microwave devices using the cold noise power measurement technique. The noise source can enhance measurement accuracy by providing a calibrated noise temperature directly at the device reference plane. A procedure to determine the excess noise ratio of the noise source is presented. Noise figure measurements performed up to 40 GHz with the on-wafer noise source and with a commercial coaxial noise source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Therefore, the standard microstrip cannot meet the requirement. An aperture-coupled multilayer microstrip antenna (ACMMA) possesses wide band and, furthermore, 40% fractional impedance bandwidth has been obtained [2]. In addition, this type of configuration has the following advantages [2,3]:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the standard microstrip cannot meet the requirement. An aperture-coupled multilayer microstrip antenna (ACMMA) possesses wide band and, furthermore, 40% fractional impedance bandwidth has been obtained [2]. In addition, this type of configuration has the following advantages [2,3]:…”
Section: Discussionmentioning
confidence: 99%
“…1) without requiring an input coaxial-to-on-wafer adapter, therefore, a correction of the input-adapter losses is not necessary and the inaccuracies associated with the measurement of its insertion-loss are reduced; (ii) the ENR level at the on-wafer reference plane is higher, thus reducing noise figure measurement uncertainty. A number of devices have been proposed in the literature as on-wafer noise sources, for example, avalanche diodes [1], resistive devices [2], and Cold-FETs [3]. In [1], the ENR of the avalanche noise diode is computed from its noise temperature, which is measured by using a receiver calibrated with cryogenic and room-temperature standards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise sources based on active devices such as FETs in a one-port configuration have been proposed in the literature [1][2][3] as an alternative to avalanche-noise diodes (normally included in coaxial and waveguide noise sources) [4,5] and other devices [6]. In [1], a FET is used as an equivalent "cold" source, and more recently a FET-based cold/hot noise source [2] has been proposed, where the selection between states is obtained through device-bias control and switching the device input port between the gate-source and drain-source ports, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…While FET-based noise sources present the advantage of being easily compatible with microwave on-wafer measurement systems [7], it is necessary to know their excess noise ratio (ENR) in a wide frequency range, in order to be able to calibrate the noise receiver. To determine the noise-source ENR, usually its output-noise temperature is measured with a receiver previously calibrated, using a well-known room-temperature and/or cryogenic noise reference [1][2][3][4]6]. In a preceding work [5], it has been shown that equivalent noise models for the noise devices are useful in the determination of their ENR, because they help to reduce measurement uncertainty, in particular, when the device's reflection-coefficient magnitude is high, as occurs in unmatched on-wafer FET or avalanche-diode-noise sources.…”
Section: Introductionmentioning
confidence: 99%